Vallejo's maps in Trilce - del Rosario Angleró, Margarita (2022)
A first reading of Trilce causes complete bewilderment, and it is clear that this discomfort is one of the features of its aesthetic meaning. The outline of a poetic «map» of Vallejo could illuminate or guide readers to the sense of disorientation experienced in the reading of his poems. Although Vallejo does not mark a visual map on the page or canvas like other avantgarde poets, in Trilce the map is sketched by words that allude to the geography of an uncertain place: body, house, prison, to name but a few. In this sense, this article outlines a possible mapping of the poems «XIX», «XXXVI», «Trilce», as well as their relationship with the collection of poems España, aparta de mi este cáliz.